2019
DOI: 10.1002/tsm2.110
|View full text |Cite
|
Sign up to set email alerts
|

Using real‐time biofeedback to alter running biomechanics: A randomized controlled trial

Abstract: In this study, we assessed the effectiveness of a mobile feedback system on transitioning runners to a non‐rearfoot strike (NRFS) pattern and prospectively compared injury incidence rates at one year between rearfoot strike (RFS) and NRFS runners. 128 RFS runners participated in a 2‐hour training session to learn a NRFS pattern with 114 completing the 1‐year follow‐up. Participants were randomized into a control group (CON) with no additional training and a biofeedback group (BFG) where they received equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…Perhaps the runners with knee pain sustained injury because of their inability to withstand this loading and a subsequent inability to adapt their mechanics to dissipate these loads appropriately. In addition, it appears that only 1 55 of 2 intervention studies 52 , 55 found a beneficial effect of FST modification (changing from RFS to non-RFS) in RRI reduction, and both of these studies had poor study design, very low level of evidence (as measured using the GRADE assessment approach), and low participant numbers, further supporting the main findings of this systematic review.…”
Section: Discussionsupporting
confidence: 66%
“…Perhaps the runners with knee pain sustained injury because of their inability to withstand this loading and a subsequent inability to adapt their mechanics to dissipate these loads appropriately. In addition, it appears that only 1 55 of 2 intervention studies 52 , 55 found a beneficial effect of FST modification (changing from RFS to non-RFS) in RRI reduction, and both of these studies had poor study design, very low level of evidence (as measured using the GRADE assessment approach), and low participant numbers, further supporting the main findings of this systematic review.…”
Section: Discussionsupporting
confidence: 66%
“…The primary outcome for this study was a NRFS running pattern and the secondary outcome of interest was AVLR. Based on an a priori power analysis (G * Power, version 3.1.9.2, Heinrich-Heine-Universitat Dusseldorf, Dusseldorf, Germany) of previously published data (Goss et al, 2015;Morris et al, 2020) using AVLR and cadence for a large effect size (Cohen's d = 0.80) with α set at 0.05, we determined at least nine participants were required for adequate power. To account for an above average attrition and possible injury or re-injury rate, we aimed to enroll a total of 23 runners.…”
Section: Methodsmentioning
confidence: 99%
“…Secondarily, we examined pain scores, functional outcome measures, AVLR, cadence, peak vGRF, and stance time throughout the training protocol. We hypothesized the instrumented socks would enable approximately 50% of previously injured runners to transition from a RFS to a NRFS running pattern (Morris et al, 2020). Additionally, we hypothesized that the runners who transitioned to a NRFS pattern would exhibit no increase in pain, increased functional outcome scores, decreased AVLR, increased cadence, and reduced stance time (Miller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Continued* The most commonly investigated biomechanical components from a recent systematic review on the relation between running technique and running injuries among prospective studies (Ceyssens et al, 2019) are included in this figure. Four additional prospective studies that were published after the search of the systematic review was finished were also included (Becker et al, 2018;Morris et al, 2019;Shen et al, 2019;Winter et al, 2019). The methodological quality of these studies was determined using a modified Downs and Black scale (Downs & Black, 1998) from Ceyssens et al (2019) and can be found in supplementary file I.…”
Section: No Evidence Availablementioning
confidence: 99%